A new species and updates on the Rhagovelia angustipes complex (Hemiptera, Heteroptera, Veliidae) in Colombia - Galindo-Malagón, Ximena Alejandra; Morales, Irina; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2023)
Rhagovelia Mayr, 1865 (Hemiptera, Heteroptera, Veliidae) is a diverse genus of small to medium-sized true bugs that live on the surface of the water, preferentially in lotic environments with moderate to strong current. The Rhagovelia angustipes species complex is particularly speciose in Colombia, and has recently been the subject of a revision. Nonetheless, new species of the complex are still being discovered in the country. We present here the description of Rhagovelia andradei sp. nov., collected on the eastern Colombian Andes, new records for three other species, R. calceola, R. gastrotricha and R. molanoi, an updated key, and a summary of the distribution of the complex in the country.